Perbandingan Pembelajaran PPKN SD di Kurikulum 2013 dengan Kurikulum Merdeka - Tesa Lisforti (STIKes Ibnu Sina Ajibarang, 2024)
In Indonesia, education cannot be separated from human life. One way to obtain knowledge is the teaching and learning process in schools and this is the implementation of education. To implement the materials or teaching materials used in schools requires something that covers it, namely the curriculum. In Indonesia, the curriculum changed a lot starting from 1947 until the independent curriculum. Hi, this is done to improve the previous curriculum and also to make the curriculum updated or keep up with the times. Likewise with the PPKN SD curriculum, which from the past until now has seen many good improvements. This is done so that good character values ​​remain and also makes Pancaila a way of life. This aims to face increasingly rapid changes in the times and enforce the law and comply with necessary regulations. applied since childhood. In this research, researchers used a literature study or literature review method. By utilizing this literature study, we succeeded in getting a comparison of PPKN learning in the 2013 curriculum with the independent curriculum.